Desain Model Parameter dan Monitoring Panel Surya Menggunakan IOT - Selamat Meliala; Faisal Manurung; Raihan Putri; Asran Asran; Teuku Multazam (Fakultas Teknik, 2023)
AbstractUtilizing sunlight to then be converted solar energy through a solar panel process to produce unidirectional electrical energy. Solar panel monitoring still uses a lot of manual measuring tools and records measurement results manually which requires quite a lot of human power, both on a small and large scale. Writing this research will discuss designing a monitoring and recording system for 30 WP solar panel data based on the Internet of Things and discuss the tilt angle of the solar panel and the elevation angle of the sun which affect the output of the solar panel with a battery load and a 12 volt DC lamp. The method in this design is divided into two, namely hardware design and software design. This tool uses Arduino Uno as a controller, NodeMCU as internet media, and an SD Card as a solar panel parameter data recorder. Based on the results and discussion of the tool designed to be able to monitor solar panel parameters for 7 hours per day and monitoring is carried out for 11 days. Data shows that solar panels can produce maximum power during testing on December 27, 2021 of 40 W at a tilt angle of 28° with an efficiency of 75.76% and a fill factor of 60.20%. The lowest power generated by solar panels during testing on January 3, 2021 was 26.55 W at a tilt angle of 27° with an efficiency of 85,247and a fill factor of 39.97%.Keywords: solar panels, internet of things, data recorders, monitoring, tilt angles